PERAN SERTA UMAT DALAM MENGEMBANGKAN KOMUNITAS BASIS GEREJAWI: Studi Kasus KBG St. Rafael, Paroki St. Perawan Maria, Keuskupan Pangkalpinang - Ramti, Agatha; Hendra, Alexander (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
The research discusses about the roles of parishioners in developing Komunitas Basis Gerejawi (KBG)/Basic Ecclesial Communities (BECs) at St. Rafael, St. Mary the Virgin, in the Diocese of Pangkalpinang. KBG represents the unique model of faith formation that has been developed in the Diocese of Pangkalpinang. The research employs on case study approach. Case study approach investigates a contemporary phenomenon in depth and within its real-world context, namely, the development of KBG in Indonesia, especially in the Diocese of Pangkalpinang. The research involves 8 informants and 2 validators. The result show that (1) the parishioners are involved in attending the meeting actively; (2) the parishioners are involved in religious activity at KBG; (3) the parishioners are also involved in developing solidarity, even though it has not been the main concern. As a conclusion, the research argues that KBG St. Rafael confirms the fact that KBG in Indonesia is different from its roots, namely, KBG in Latin America. KBG in Indonesia plays an important role primarily as religious organizations that helps simple people to nurture their faith. Solidarity and social action appear to be the secondary purpose in KBG.